Effect of thickness of SiC films on compression and thermal properties of SiC/CF composites. Issue 4 (March 2019) - Ye, Xinli; Chen, Zhaofeng; Ai, Sufen; Hou, Bin; Zhang, Junxiong; Zhou, Qianbo; Liu, Hezhou; Cui, Sheng
Abstract: Commonly, carbon foam derived from commercially available melamine foam showed brittle characteristics. In this paper, the carbon foam was prepared via the direct carbonization of the melamine foam, and chemical vapor deposition was employed to deposit ultra-thin SiC films on the CF skeleton. The evolution, microstructure, mechanical strength, and thermal properties of the as-prepared SiC/CF composites were investigated. Test results showed that a novel SiC skeleton with a three-dimensional interconnected network was prepared successfully. The thickness of the SiC filmes had a significant influence on the compression and thermal properties of the composites. The SiC/CF-II possessed a higher compression performance than that of SiC/CF-I, while the thermal insulation was relatively much poorer. This present work had some reference meaning to the correlation studies of the thermal insulation material for the potential applications while bearing live loads.